(untitled) - Adams, Ansel (Boston, 1979)
The book contains poster classics like "Clearing Winter Storm, Yosemite Valley, 1944, Moon and Half Dome, Yosemite Valley, 1960, and Winter Sunrise, Sierra Nevada, from Lone Pine, 1944." Non students of Mr. Adams will discover many "unseen" photographs that are beautiful in their own right but did not have the mass-market appeal of his classics. Too valuable to be a coffee table book, this collection is the archetype for fine art books
Keywords: Landscape photography,Yosemite national park,Vườn quốc gia Yosemite,Chụp phong cảnh; Yosemite national park,Pictorial works; California